Karakteristik Kaum Homeless Di Kota Kendari dan Konsepsi Mereka terhadap Rumah Tinggal - La Iba (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2015)
The rapid growth of the city turned out to carry a variety of problems. One of the problemsMis the increasing number of urban poor settler. They can be found in every corner of the city and living as beggars, scavengers, unskilled laborers, and other informal sectors workers. Poverty and limited buying power to force them to take shelter in a doorway, around the bridge, in the traditional markets, etc. Nevertheless, some also try to survive by making temporary house which is built in accordance to their concept of house. Their particular concepts of physical house is quite interesting to study. This study investigated how the process and the background of becoming homeless. The approach used is the homelessness approach in a global perspective such as climate, culture, housing, and job-seeking. The study found that there are some criteria of homeless in the city of Kendari. There are people who sleep in any place, move, and who stay at home with makeshift construction or not appropriate eligibility rules and legality predetermined laws. Most of them live in rural part of Kendari because this is the central development of the city of Kendari and tend to provide more opportunity for informal sector to develop. The lack of identity cards (Kartu Tanda Penduduk- KTP) become one of the most significant issues for the lack of access to the procurement of the home, education, health and other matters, especially in recognition of their existence. Keywords: city, poverty, homeless.